Coronary Artery Bypass Graft Surgery Improves Survival Without Increasing the Risk of Stroke in Patients with Ischemic Heart Failure in Comparison to Percutaneous Coronary Intervention: A Meta-Analysis With 54,173 Patients - Sá,Michel Pompeu Barros Oliveira (2019)
Abstract Objective: To evaluate whether there is any difference on the results of patients treated with coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI) in the setting of ischemic heart failure (HF). Methods: Databases (MEDLINE, Embase, Cochrane Controlled Trials Register [CENTRAL/CCTR], ClinicalTrials.gov, Scientific Electronic Library Online [SciELO], Literatura Latino-americana e do Caribe em Ciências da Saúde [LILACS], and Google Scholar) were searched for studies published until February 2019. Main outcomes of interest were mortality, myocardial infarction, repeat revascularization, and stroke. Results: The search yielded 5,775 studies for inclusion. Of these, 20 articles were analyzed, and their data were extracted. The total number of patients included was 54,173, and those underwent CABG (N=29,075) or PCI (N=25098). The hazard ratios (HRs) for mortality (HR 0.763; 95% confidence interval [CI] 0.678-0.859; P<0.001), myocardial infarction (HR 0.481; 95% CI 0.365-0.633; P<0.001), and repeat revascularization (HR 0.321; 95% CI 0.241-0.428; P<0.001) were lower in the CABG group than in the PCI group. The HR for stroke showed no statistically significant difference between the groups (random effect model: HR 0.879; 95% CI 0.625-1.237; P=0.459). Conclusion: This meta-analysis found that CABG surgery remains the best option for patients with ischemic HF, without increase in the risk of stroke.